Feasibility and acceptability of research-grade wearables for health and labor capacity monitoring in the context of climate change and heat stress: the case of Nouna, Burkina Faso - Zout, Georgi; Höver, Celine; Eggert, Edgar; Gunga, Hanns-Christian; Ouermi, Lucienne; Sié, Ali; Huhn, Sophie; Bunker, Aditi; Barteit, Sandra; Mendt, Stefan; Maggioni, Martina Anna (PLOS ONE, 2025)
Current climate projections estimate a further rise of mean ambient temperatures of 1.5°C until 2040. However, the understanding of heat stress’s impact on health and labor capacity, especially in vulnerable regions such as sub-Saharan Africa, remains limited. In turn, no long-term investigations monitoring and uniting both individual-level subject and environmental data have been yet conducted in this region. To address this knowledge gap, we evaluated the feasibility and acceptability of research-grade wearables for continuous, direct, individual-level monitoring of physiological parameters in a population of subsistence farmers (one woman and one man per n=20 households) in rural Burkina Faso. We conducted a four-week pilot study, investigating data completeness and quality of heart rate and core body temperature, and data completeness for physical activity, and GPS individual tracking, simultaneously monitoring outdoor and indoor wet-bulb-globe temperature. Additionally, participants were surveyed regarding their acceptance of employed wearables. Regarding environmental indoor monitoring, we collected 85% of completed data, whereas for outdoor, it was 100%. An average of 97.5% of viable data sets were retrieved for all wearables (heart rate: 97.5%, core body temperature: 97.5%, physical activity: 97.5%, GPS: 97.5%). Individual data point completeness was > 92% for all sensors, except GPS, where it was 67% on average. Acceptance of wearables was positive, with a range of 79% to 95%. The main challenges perceived by participants were missing personalized sensor feedback (70%) and uncertainty regarding the meaning of the wearables (47.5%). We show that the implementation of research-grade wearables in sub-Saharan Africa is technically feasible and socially accepted. Further, we point out current challenges and provide a solid framework for future research in this region.
Gesehen am 09.12.2025